Synthesis of Saturated Benzodioxepinone Analogues: Insight into the Importance of the Aromatic Ring Binding Motif for Marine Odorants. Issue 3 (4th December 2014) - Plummer, Christopher M.; Gericke, Robert; Kraft, Philip; Raynor, Aaron; Froese, Jordan; Hudlický, Tomáš; Rook, Trevor J.; Jones, Oliver A. H.; Hügel, Helmut M.
Abstract: As part of our research exploring the influence of molecular variations of Calone 1951 ® on marine fragrance performance, we report the synthesis, crystal structures, and olfactory analysis of the first saturated benzodioxepinone analogues. By substitution of the aromatic moiety of the benzodioxepinone fragrance molecule with a saturated ring counterpart, we endeavoured to discover the molecular interactions of the aromatic and aliphatic rings with fragrance receptor sites, and also to shed light on any potential chiral interactions occurring within the receptor. Our results showed that an aromatic ring system is necessary for binding to the marine odour receptor(s), and that the addition of an alkene or methyl substituent has little effect on the low receptor affinity. However, a weak marine odour character was found for the 6‐methyl saturated derivatives, which could possibly be explained by superposition analysis of the respective structures, which were derived from X‐ray coordinates. Abstract : As part of our research exploring the influence of molecular variations of Calone 1951 ® on marine fragrance performance, we report the synthesis, crystal structures, and olfactory analysis of the first saturated benzodioxepinone analogues. Our results showed that an aromatic ring system is necessary for binding to the marine odour receptor(s).